Optimization of Endoglucanase Production from a Novel Bacterial Isolate, Arthrobacter sp. HPG166 and Characterization of Its Properties - Shengwei Huang; Guanjun Deng; Ying Yang; Zhengyan Wu; Lifang Wu (Brazilian Archives of Biology and Technology, 2015)
ABSTRACTIn this study, a potential novel cellulolytic bacteriumArthrobacter sp. HPG166 was isolated from the hindgut of root-feeding larvaeHolotrichia parallela. Optimization of fermentation factors for endoglucanase production byArthrobacter sp. HPG166 was carried out via response surface methodology. Sodium carboxymethylcellulose 1.19% (w/v) and beef extract 0.35% (w/v) were the ideal combination of carbon and nitrogen sources for enzyme production; the optimum temperature and pH for cellulase production were 34°C and pH 8.0 respectively. Under the optimized fermentation conditions, the maximum endoglucanase activity of 1.411 U mL-1 was obtained. The crude endoglucanase was thermotolerant as it retained 50.31% of its activity after incubation at 70°C for an hour. Metal profile of the enzyme indicated that Mg2+ and Na+ were strong stimulators while Mn2+ and Co+ drastically inhibited its activity. Due to its particular characteristics, this enzyme could have potential for industrial applications.